2007
DOI: 10.1103/physrevb.75.014208
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of thermodynamic properties and clustering in the bcc Fe-Cr system

Abstract: Iron-chromium alloys are characterized by a complex phase diagram, by the small negative enthalpy of mixing at low Cr concentrations in the bcc ␣-phase of Fe, and by the inversion of the short-range order parameter. We present Monte Carlo simulations of the binary Fe-Cr alloy based on the cluster expansion approximation for the enthalpy of the system. The set of cluster expansion coefficients is validated against density functional calculations of energies of small clusters of chromium in bcc structure. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 43 publications
10
66
0
Order By: Relevance
“…Kinetic Monte Carlo (KMC) simulations performed by Bonny et al [24,25] showed that most of the Cr-rich precipitates (containing more than 95 at.% Cr) initially have sphere-like shapes in the Fe-(11.8-18)Cr matrix. In contrast to that, the Monte Carlo simulations based on the cluster expansion approximation done by Lavrentiev and co-workers [18] and Lavrentiev et al [26] predicted a clear polyhedral shape for the pure Cr cluster in the a phase containing about 10 at.% Cr and at 0 K. All above compositions for the interfaces are located in the bottom-left corner (x, y90:2) of Fig. 2 (i.e., for those alloys we have g 001 =g 110 91:2) and, therefore, the present study confirms the KMC results by Bonny et al [24,25]).…”
Section: According Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic Monte Carlo (KMC) simulations performed by Bonny et al [24,25] showed that most of the Cr-rich precipitates (containing more than 95 at.% Cr) initially have sphere-like shapes in the Fe-(11.8-18)Cr matrix. In contrast to that, the Monte Carlo simulations based on the cluster expansion approximation done by Lavrentiev and co-workers [18] and Lavrentiev et al [26] predicted a clear polyhedral shape for the pure Cr cluster in the a phase containing about 10 at.% Cr and at 0 K. All above compositions for the interfaces are located in the bottom-left corner (x, y90:2) of Fig. 2 (i.e., for those alloys we have g 001 =g 110 91:2) and, therefore, the present study confirms the KMC results by Bonny et al [24,25]).…”
Section: According Tomentioning
confidence: 99%
“…In particular, the calculated anomalous negative mixing enthalpy at low Cr concentration, the threshold behavior of the surface concentration profile, or the peculiar alloying effects on the cubic elastic constants were all shown to be attributed to magnetism and to the particular Fermisurface topology [4,[13][14][15][16][17][18][19][20][21][22][23]. In order to obtain important information about the Cr-rich precipitates in Fe-Cr alloys, such as structure, mean size, number density, composition, and shape, several Monte Carlo simulations have been performed [18,[24][25][26]. For the Fe-Cr alloy with different compositions, after annealing for a period of time, the Cr or Cr-rich precipitates were found to have different shapes, either polyhedron or sphere-like.…”
mentioning
confidence: 98%
“…LaSalle and Schwartz [18] investigated two different solution treatment temperatures of 850 and 1200°C and also found that the lower temperature gave faster decomposition upon subsequent aging. Furthermore, it has been found, both theoretically and experimentally, that there is a positive atomic short range order (SRO), i.e., clustering, above the miscibility gap in concentrated Fe-Cr alloys above about 10 at.% Cr [19][20][21][22][23]. Recently, Zhou et al [24] have reported atom probe tomography (APT) observations of the clustering of Cr in the bcc phase of ferritic and duplex stainless steels after solution treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In rigid lattice MC simulations [12,20,[34][35][36][37] using Ising-type interaction the Hamiltonian must be made temperature dependent. Semiempirical potentials have been used in both Metropolis MC (MMC) [38][39][40] and kinetic MC (KMC) [9,[41][42][43][44][45][46][47] studies.…”
Section: B Large-scale Monte Carlo Simulationsmentioning
confidence: 99%